Dynamic analysis of an open-loop proportional valve controlled hydrostatic drive. (December 2019) - Dasgupta, K; Ghoshal, Sanjoy K; Kumar, Sujit; Das, J
This article highlights the dynamic analysis of a proportional valve controlled hydrostatic drive. Such drives are used widely in construction and mining applications. In the drive considered for the analysis, the speed of a bent-axis hydro-motor is controlled by varying flow supplied through a proportional direction controlled valve. A non-linear mathematical model using bond graph simulation technique is developed, where detailed model of the drive system including its loading arrangement is incorporated. From the test results of the pressure-flow characteristics of the valves, its port resistances are identified. Using them and taking into account various losses of the hydro-motor, the drive model is validated through experiments. The verified model is used to study the effects of the perturbations of some critical parameters on the transient responses of the hydrostatic drive through simulation. The proposed model may be useful for initial design of such drive and the development of control systems where these drives are used as actuators.